Digital Inclusive Finance and its Role in Driving SME Performance: Evidence from Data Analytics - Gbadebo, Adedeji Daniel (International Journal of Economics and Financial Issues, 2025)
The research work concerns itself with the role of inclusive finance through digital means on the development of small and medium-sized enterprises (SMEs) in a data-informed method of study. Using cross-sectional survey data of 328 SMEs, we use descriptive statistics, correlation analysis, and multiple regressions to investigate the correlation and relationship between the digital finance adoption/a Digital Inclusive Finance Index and mobile credit access and SME performance indicators of return on assets (ROA) and revenue growth. Findings indicate that digital inclusive finance leads to positive changes in the profitability and growth of the SMEs (profitability increases by 103 percent, and the growth increases by 85 percent), and the effect is stronger in the firms in the process of strengthening their digital foundation who worked with a better digital infrastructure. The paper agrees that the growth in digital financial services and infrastructure has become essential in the development of SMEs. To enhance the benefits of inclusive finance through digital finance, we suggest precise policy measures to enhance the digital infrastructure, increase digital literacy, and establish collaborations between financial institutions and fintech provider to maximize the benefits of digital to SMEs.